DESAIN MODUL PEMBELAJARAN MATAKULIAH PRAKTIK KERJA KAYU PADA FAKULTAS TEKNIK UNIVERSITAS NEGERI MAKASSAR - Panennungi T; Onesimus Sampebua; Rahmansah (Universitas Negeri Makassar, 2023)
This research aims to create a learning module or woodworking practice courses at the Department of Civil Engineering and Planning Education. The learning modules for the woodworking practice course that will be made include practices of sawing, using a four-plane manual planer, four-plane planes with a machine, straight lip joints, hooked straight lips, oblique lip joints, oblique lip joints hook, and workpiece manufacture.The method used in this research is the research and development method, such as data collection, module design, module validation by experts, module revision, until the module can be used.